Colloidal PbS Nanosheets with Tunable Energy Gaps. Issue 1726 (15th May 2015) - Jiang, Zhoufeng; Khan, Simeen; Premathilake, Shashini; Bhandari, Ghadendra; Subedi, Kamal; He, Yufan; Leopold, Matthew; Reilly, Nick; Lu, Peter; Zayak, Alexey; Sun, Liangfeng
ABSTRACT: Ultrathin colloidal PbS nanosheets are synthesized using organometallic precursors with chloroalkane cosolvents, resulting in tunable thicknesses ranging from 1.2 nm to 4.6 nm. We report the first thickness-dependent photoluminescence spectra from lead-salt nanosheets. The one-dimensional confinement energy of these quasi-two-dimensional nanosheets is found to be proportional to 1/L instead of 1/L 2 ( L is the thickness of the nanosheet), which is consistent with results calculated using density functional theory as well as tight-binding theory.